Importance of banks first floor in the income, and grant of probate of rediscount's credits in Colombia (2013)
FINAGRO , is a second-tier bank backed by the Government aimed at growth and development of the agricultural sector , where the main source of income apart from the contributions made by the Government and its shareholders are in Titles TDA Agricultural Development , which are investments in which are required all financial intermediaries to perform , these investments generate very low returns because the interest rate for these securities is DTF - 2 or 4 points according to the class of securities .